2016
DOI: 10.1093/brain/aww003
|View full text |Cite|
|
Sign up to set email alerts
|

Network-selective vulnerability of the human cerebellum to Alzheimer’s disease and frontotemporal dementia

Abstract: SEE SCHMAHMANN DOI101093/BRAIN/AWW064 FOR A SCIENTIFIC COMMENTARY ON THIS ARTICLE: Neurodegenerative diseases are associated with distinct and distributed patterns of atrophy in the cerebral cortex. Emerging evidence suggests that these atrophy patterns resemble intrinsic connectivity networks in the healthy brain, supporting the network-based degeneration framework where neuropathology spreads across connectivity networks. An intriguing yet untested possibility is that the cerebellar circuits, which share ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 56 publications
13
120
0
Order By: Relevance
“…In addition, our combined plot showed that there exists some overlap in atrophy patterns. These findings suggest that cerebellar changes are highly disease-specific and correspond to the cortical or subcortical changes characteristically reported in each disease 10. Lobular overlap between ALS and FTD in Crus I/II further corroborates this notion as both diseases lie on a spectrum.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, our combined plot showed that there exists some overlap in atrophy patterns. These findings suggest that cerebellar changes are highly disease-specific and correspond to the cortical or subcortical changes characteristically reported in each disease 10. Lobular overlap between ALS and FTD in Crus I/II further corroborates this notion as both diseases lie on a spectrum.…”
Section: Discussionsupporting
confidence: 72%
“…Regions of Crus I/II identified here share major connections with prefrontal and parietal areas as part of the DMN and ECN,40 resulting in coactivation during executive functioning, memory and emotion processing 48. This may explain the relationship between cerebellar atrophy and specific cortical changes in FTD 10. The atrophied regions in Crus I may also be involved in the SN, which has been recognised to be affected by degeneration in FTD 10…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the cerebellum can be parsed functionally and morphologically into different subdivisions and it is likely that AD pathology targets each subdivision differently. Previous voxel-based morphometric studies showed bilateral lower gray matter density in lobule VI (Colloby, et al, 2014) and Crus I/II (Guo, et al, 2016) in AD compared with CN, suggesting that network-selective vulnerability underlies the cerebellar neurodegeneration(Guo, et al, 2016). Regardless of selective or non-selective volume loss in the cerebellum and its subregions, cross-sectional approach needs to be affirmed by tracking atrophy in a longitudinal approach.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, recent data indicate that AD-related neurodegeneration is present, beyond the cortex, also in the Crus I and II cerebellar regions (Guo et al, 2016). In that respect, it is conceivable that the modafinil FC effects we have found in these cerebellar areas may be of some help and exert a compensatory role.…”
Section: Resultsmentioning
confidence: 99%